International Marketing Management: PT. Sampoerna Tbk - Abdi Suryo Laksono; Marcel Marcel; Daisy Mui Hung Kee; Liu Mengjiao; Loh Yi Fang; Low Xin Yi; M. I. Mahavira Zein (AIBPM Publisher, 2020)
The announcement of the cigarette excise tax increase made on September 13, 2019 was very surprising, but Sampoerna respected the President's decision. At present, Sampoerna is working to determine how to manage the impact of the increase. While waiting for the details of the excise tax policy to be officially released, Sampoerna intends to submit two recommendations to the Government to support the continuation of employment.